Damage by the green-belly stink bug to corn - Fernandes, Paulo Henrique Ramos; Ávila, Crébio José; Silva, Ivana Fernandes da; Zulin, Daniele (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the potential damage of the green-belly stink bug, Dichelops melacanthus, to corn in greenhouse and field conditions. Three trials were carried out. In the greenhouse, corn plants in the V1 stage were evaluated after each of them was infested with one insect in four developmental stages (nymphs of the third, fourth, and fifth instars and adults) during 14 days. In the field, corn plants in four developmental stages (V1, V3, V5, and V7) were infested inside cages with five adult stink bugs, also during 14 days. In another trial in the greenhouse, the same treatments of the field trial were conducted during 14 days, but with an infestation intensity of one bug per plant per pot. The control treatment was without infestation. In all trials, damage scores were attributed to the corn plants and the dry matter of the aerial part of the plants was determined. In the field, stem diameter and grain yield were also evaluated. Third-instar nymphs do not cause significant changes in the dry weight of the aerial part of the plant and in the damage scores, compared with the control treatment. Infestations by adult stink bugs cause more damage to corn plants in the V1 and V3 stages, both in field and greenhouse conditions.